Marketing action to promote cycling. - (:unkn) unknown (My University, 2012)
Today marketing actions are instruments in the toolbox of cycling promotion that have proven successful in selling everything around cycling through creative and targeted measures. Bike actions can emotionalise cycling. They can reach new target groups and create a good atmosphere . (Difu)
Keywords: Individualverkehr; Fahrradverkehr; Öffentlichkeitsarbeit; Fahrradnutzung; Fahrradbenutzung; Radverkehrsförderung; Marketing